Uptake and Subcellular Compartmentation of Gibberellin A(1) Applied to Leaves of Barley and Cowpea - Ohlrogge, John B. (1980)
The uptake and subcellular accumulation of gibberellin A(1) (GA(1)) by leaves and protoplasts of barley (cv. Numar) and cowpea (cv. Blackeye pea No. 5) were investigated. Uptake of GA(1) by cowpea leaves is optimal at pH 5.8 and occurs by a saturable, probably carrier-mediated process having a half-maximal velocity at 10 to 20 micromolar. Uptake by both barley and cowpea leaves is inhibited by low temperature (+4 C) and the metabolic inhibitors 2,4-dinitrophenol and azide and is stimulated by ATP. Mesophyll protoplasts isolated from leaves fed radioactive GA(1) retain 20 to 80% of the radioactivity incorporated by excised leaves. The subcellular localization of the [(3)H]GA was determined by lysing protoplasts and separating subcellular organelles by density gradient centrifugation. Less than 5% of the incorporated [(3)H]GA was found associated with chloroplasts, mitochondria, nuclei, or other organelles or membranes with densities in sucrose gradients greater than 1.15 grams per cubic centimeter. Fifty to 100% of the [(3)H]GA was found in vacuoles. Isolated vacuoles were judged to be free of contamination by cytoplasm using phosphoenolpyruvate carboxylase as a marker enzyme. Osmotic breakage of vacuoles or protoplasts released > 95% of the [(3)H]GA, suggesting that GA is associated with the vacuolar sap rather than with the tonoplast membrane.